PERAN ETIKA ADMINISTRASI PUBLIK DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN YANG BERSIH DAN TRANSPARAN - Kholifatus Sya’diyah; Salsabilla Azzahra Niesma Putri; Hayat, Hayat (Cahaya Ilmu Bangsa, 2025)
Public administration ethics is essential to achieve transparent governance. This ethic includes integrity, transparency, accountability and justice to combat corruption and nepotism. Applying this ethic fosters an efficient and fair government that prioritizes the interests of society. This article discusses the strategic impact of ethics in improving the quality of public services, public trust, and bureaucratic reform through transparency and participation. It also discusses challenges in implementing ethics, such as corruption and inadequate oversight, and proposes solutions such as ethics education and meritocracy. By promoting strong ethical standards, credible and accountable governance that is aligned with the public interest can be realized.